2003
DOI: 10.1093/pasj/55.1.l1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced HCN (1-0) Emission in the Type-1 Seyfert Galaxy NGC 1097

Abstract: The central kpc region of the low luminosity type-1 Seyfert galaxy NGC 1097 has been observed in the CO(1-0) and HCN(1-0) lines with the Nobeyama Millimeter Array and the NRO 45 m telescope. We find a striking enhancement of the HCN emission toward the active nucleus of NGC 1097; a large fraction of the CO emission comes from the circumnuclear starburst ring (r ∼ 10 ′′ or 700 pc at D = 14.5 Mpc), whereas the HCN emission is dominated by a strong unresolved peak at the nucleus. The HCN-to-CO integrated intensit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
97
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(107 citation statements)
references
References 40 publications
10
97
0
Order By: Relevance
“…As noted by Kohno et al (2003), HCN is observed to be significantly enhanced toward the nucleus relative to CO which might point out HCN as a not the ideal candidate to become a reference molecule. However, this HCN/CO trend gets less evident when higher J transitions of CO are considered (Hsieh et al 2012).…”
Section: Relative Molecular Abundancesmentioning
confidence: 94%
“…As noted by Kohno et al (2003), HCN is observed to be significantly enhanced toward the nucleus relative to CO which might point out HCN as a not the ideal candidate to become a reference molecule. However, this HCN/CO trend gets less evident when higher J transitions of CO are considered (Hsieh et al 2012).…”
Section: Relative Molecular Abundancesmentioning
confidence: 94%
“…2) or other dense gas tracers at comparable resolution (Kohno et al 2003;Hsieh et al 2008). Instead the CO intensity peaks near the contact points and is much fainter over the rest of the ring.…”
Section: Herschel Pacs Observations Of the Circumnuclear Ring In Ngc mentioning
confidence: 95%
“…The KINGFISH project (Key Insights on Nearby Galaxies: a FarInfrared Survey with Herschel, PI: R. C. Kennicutt) is an opentime Herschel key program that aims to measure the heating and cooling of the gaseous and dust components of the ISM in a sample of 61 nearby galaxies with the PACS and SPIRE instruments. The FIR spectral range covered by PACS includes several of the most important cooling lines of the atomic and ionized gas, notably [C ii] NGC 1097 is a Seyfert 1 galaxy with a bright starburst ring with a diameter of 2 kpc and a strong large-scale stellar bar (Gerin et al 1988;Kohno et al 2003;Hsieh et al 2008) with a length of 15 kpc. This bar may be responsible for driving gas into the central region of the galaxy, forming a ring of gas near the Inner Lindblad Resonance, triggering the formation of massive star clusters (e.g., Athanassoula 1992).…”
Section: Introductionmentioning
confidence: 99%